Aurora kinase inhibitors: a patent review (2014-2020) - Jing, Xue-Li; Chen, Shi-Wu (Expert opinion on therapeutic patents, 2021)
: Aurora kinases are a family of serine/threonine kinases, and promote mitotic spindle assembly by regulating centrosome duplication and separation. Aurora kinases are overexpressed in a variety of tumor cell lines, thus, the use of Aurora kinase small-molecule inhibitors has become a potential treatment option for cancer. : As a continuing review of Aurora kinase inhibitors and their patents published in 2009, 2011 and 2014. Herein, we updated the information for Aurora kinase inhibitors in clinical trials and the patents filed from 2014 to 2020. PubMed, Scopus, SciFinder, and www.clinicaltrials.gov databases were used for searching the clinical information and patents of Aurora kinase inhibitors. : Even though Aurora A or B selective as well as pan inhibitors show preclinical and clinical efficacy, so far, no Aurora kinase inhibitor has been approved for clinical use. Preliminary evidence suggested that highly selective Aurora kinase or multi-target inhibitors as a single agent as well as in combination therapy are still the current main development trend of Aurora kinase inhibitors.